THE CORRELATION BETWEEN ENGLISH LISTENING HABIT AND VOCABULAARY MASTERY AT SMA KATOLIK St. F.X. KEMA - Jean Motoh; Noldy Pelenkahu; Olga A. Rorintulus (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of the study is to find out if there is a correlation between English listening habit and vocabulary mastery at SMA Katolik St. F.X. Kema. This is a quantitative research. This research was conducted at SMA Katolik St. F.X. Kema. A questionnaire with 15 items and vocabulary test 15 items adapted from previous related research was used and distributed to 15 students. The result of calculation was using Pearson product moment formula process by SPSS IBM Statistic Version 25 Program which showed the score of r table (-2,58<0. 606), It means that H0 was accepted and Ha was rejected. In conclusion, there is negative correlation meaning that English listening habit and vocabulary mastery at SMA Katolik St. F.X. Kema has no correlation.